2019
DOI: 10.3390/app9183875
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Pressure Pipette Aspiration Method Combined with Finite Element Analysis for Isotropic Materials

Abstract: A measurement setup combined with a numerical simulation by a linear finite element analysis is presented as a method to determine the elastic modulus of both artificial and real tissue as a function of frequency. At the end, the future goal is to develop and validate the method to measure the elastic modulus of in-vivo human vocal folds over the human phonation frequency range. In the present study, a miniaturized acoustic pressure pipette aspiration technique is developed to measure the material characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…Based on the work of Weiss et al [ 20 ] and Maghzinajafabadi et al [ 13 ], the dynamic elasticity measurements of soft tissue using pipette aspiration have been further developed. Figure 3 and Figure 4 show the measurement setup with the 3D printed pipette, which is pressed at the middle of the anterio-posterio line of the VF, with a certain force, estimated by the mentioned load cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the work of Weiss et al [ 20 ] and Maghzinajafabadi et al [ 13 ], the dynamic elasticity measurements of soft tissue using pipette aspiration have been further developed. Figure 3 and Figure 4 show the measurement setup with the 3D printed pipette, which is pressed at the middle of the anterio-posterio line of the VF, with a certain force, estimated by the mentioned load cell.…”
Section: Methodsmentioning
confidence: 99%
“…The pipette aspiration technique (PipAsT) does have the potential to be miniaturized and used in an endoscopic device for in-vivo measurements, similar to a device proposed by Tran et al, with the advantage of dynamic measurements [9]. Multiple studies on dynamic measurements on silicone samples can be found [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%